Rekonsiliasi dalam Ajaran Kristen: Kontribusi terhadap Harmoni Multireligius dalam Kerangka Moderasi Beragama - Marde Christian Stenly Mawikere; Sudiria Hura (Jurnal Teologi Berita Hidup, 2024)
This article delves into the notion of reconciliation as presented in Christian doctrine and examines its significance in the context of religious moderation for promoting interfaith harmony in Indonesia. The objective of this study is to elucidate the principles of reconciliation within Christian teachings and discern the implications of this concept within the realm of religious moderation. The research methodology employed is a literature review, with a primary focus on analyzing the theology of reconciliation and its incorporation into religious moderation. The findings of this research underscore that Christian teachings concerning reconciliation encompass values such as forgiveness, peace, and inner transformation. These values align with the essence of religious moderation, which encourages dialogue, tolerance, and interfaith cooperation. The implications of these reconciliation principles from Christian teachings for religious moderation exhibit substantial potential in fostering interfaith harmony in Indonesia. To attain this objective, it is evident that these teachings play a pivotal role in shaping an all-encompassing and peaceful society within the context of existing religious diversity, thereby offering significant potential to fortify the harmonious coexistence of various religions in Indonesia.